Sensory Profiling of Indonesian White Tea Using Quantitative Descriptive Analysis - Firman Hadiansyah; Dase Hunaefi; Nancy Dewi Yuliana; Philipp Fuhrmann; Iryna Smetanska; Shin Yasuda (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2023)
Silver needle is a common type of white tea in Indonesia. The silver needle is produced from unbloomed pekoe, is pointed, slightly hairy, and silver in color. Quantitative descriptive analysis is a sensory evaluation method that relies on trained panelists' abilities in the experiment. The purpose of this study is to create a sensory profile of white tea from Indonesia using the QDA method. Five tea samples registered to the Indonesian National Agency for Drug and Food Control (Brand Gamboeng, Ennie 1, and Cap Pucuk from the West Java, Teh Dandang from Central Java, and Brand Heizl from East Java) were evaluated by trained panelists with extensive experience who had passed selection and training processes. Water was used as the neutralizer and crackers as the carrier. Three grams of each sample were brewed at 98°C with 150 mL of water for 7 min. Each panelist described the attribute, determined the reference, and evaluated all samples on a 15-cm scale. The results of the focus group discussion has obtained 12 lexicon sensory attributes, namely: yellow-brown, burned aroma, floral aroma, dry aroma, woody aroma, green aroma, burned flavor, green flavor, fermented flavor, floral flavor, bitter taste, astringent aftertaste, and bitter aftertaste. The results also showed that the